2016
DOI: 10.1038/srep31930
|View full text |Cite
|
Sign up to set email alerts
|

Fungal decomposition of terrestrial organic matter accelerated Early Jurassic climate warming

Abstract: Soils – constituting the largest terrestrial carbon pool - are vulnerable to climatic warming. Currently existing uncertainties regarding carbon fluxes within terrestrial systems can be addressed by studies of past carbon cycle dynamics and related climate change recorded in sedimentary successions. Here we show an example from the Early Jurassic (early Toarcian, c. 183 mya) marginal-marine strata from Poland, tracking the hinterland response to climatic changes through a super-greenhouse event. In contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…Our study supports Hypothesis 2 that carbon-decomposing genes derived from fungi are more influenced by climate changes than bacteria, consistent with the previous finding that warming favours fungal-mediated decomposition of plant litter (Pienkowski, Hodbod, & Ullmann, 2016). Our finding that soil transplantation increased the relative abundance of fungal chitin-and lignin-decomposing genes ( Figure 3) is alarming because the loss of soil recalcitrant carbon can reduce soil carbon stability, particularly in high-latitude soils, which account for one-third of the global soil carbon pool (Biasi et al, 2005).…”
Section: Soil Transplantation Over Large Transects Reflect Abrupt CLIsupporting
confidence: 92%
“…Our study supports Hypothesis 2 that carbon-decomposing genes derived from fungi are more influenced by climate changes than bacteria, consistent with the previous finding that warming favours fungal-mediated decomposition of plant litter (Pienkowski, Hodbod, & Ullmann, 2016). Our finding that soil transplantation increased the relative abundance of fungal chitin-and lignin-decomposing genes ( Figure 3) is alarming because the loss of soil recalcitrant carbon can reduce soil carbon stability, particularly in high-latitude soils, which account for one-third of the global soil carbon pool (Biasi et al, 2005).…”
Section: Soil Transplantation Over Large Transects Reflect Abrupt CLIsupporting
confidence: 92%
“…8). This indicated that the evolutionary conservation of RNA editing is essential for only a few plastid editing sites, which is a common phenomenon among angiosperms and has been verified in many cases [39].
Fig.
…”
Section: Discussionmentioning
confidence: 84%
“…During the negative CIE, pulses of isotopically light C suggest enhanced input of CO 2 into the atmosphere from volcanic sources 25 leading to increased global temperatures 34 , sufficient to provoke methane (CH 4 )-hydrate dissociation 3 . This combined with an increase in terrestrial methanogenesis and a potential positive feedback associated with the decomposition of plant litter enabling further release of CO 2 and CH 4 from terrestrial sources (for example, refs 35,36), thus created the large negative CIE and enhanced CH 4 driven global warming. Coupled ocean-atmosphere models suggest an increase in global precipitation rates of þ 9 cm per year driven by the subsequent rises in CO 2 (ref.…”
Section: Discussionmentioning
confidence: 99%